1996
DOI: 10.1518/001872096778827297
|View full text |Cite
|
Sign up to set email alerts
|

SPECIAL SECTION: Comparison of Self-Reporting of Deficiencies in Airway Management with Video Analyses of Actual Performance

Abstract: We compared the performance deficiencies of airway management captured by three types of self-reports with those identified through video analysis. The three types of self-reports were the anesthesia record (a patient record constructed during the course of treatment), the anesthesia quality assurance (AQA) report (a retrospective report as a part of the trauma center's quality assurance process), and a posttrauma treatment questionnaire (PTQ), which was completed immediately after the case for the purposes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Also, multiple video images can be analyzed simultaneously, offering global and continuous observational data about the OR activities as opposed to the limited view of data collection by a single observer. Most importantly, video data can be analyzed repeatedly and by multiple observers, which increases the validity and reliability of the findings [8,9]. The video-aided field study has a unique role for conducting quantitative studies on OR efficiency, error prevention, and surgical education [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple video images can be analyzed simultaneously, offering global and continuous observational data about the OR activities as opposed to the limited view of data collection by a single observer. Most importantly, video data can be analyzed repeatedly and by multiple observers, which increases the validity and reliability of the findings [8,9]. The video-aided field study has a unique role for conducting quantitative studies on OR efficiency, error prevention, and surgical education [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations were also consistent with the types of problems described during trauma resuscitation, which included poor teamwork, deficiencies in leadership, poor communication and failure to adequately perform assigned tasks. 5 Video review combined with specifically defined errors and acceptable deviations has been shown by Oakley et al 6 to be better than chart review in recognizing management and leadership errors, although less effective in recognizing items such as dosing errors, which are not easily visible. This group also noted that the absolute number of management errors was high in their trial because of the nature of video review and its superiority to clinician memory.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore horizontal coordination among planners, such as that which occurs among subordinate task forces under MOC directive, and thus model Navy's operational planning processes, we develop an optimization-based multiagent distributed planning algorithm using a blackboard as a collaborative and information sharing space. Although our distributed collaborative planning framework is motivated by operational mission planning in the Navy [14]- [16], [37], similar planning problems are faced by flight crews of commercial aircraft, collaborative software development teams, medical teams, research and development teams, to name a few [2], [20], [37], [42]. Common to these problems is a number of decision makers (DMs), generally with local goals, each one possessing a set of heterogeneous assets and having responsibility for a set of interdependent tasks.…”
mentioning
confidence: 99%